THREE IDENTITIES OF THE AUTOBIOGRAPHICAL DISCOURSE: SOME REFLECTIONS ON PEDRO NAVA’S WORK - de Barros, Mariana Luz Pessoa (Laboratório Editorial FCL-UNESP, 2012)
The diaries, letters, academic autobiographies, autobiographical novels are all genres that perform autobiographical discourse. Its key feature is not only the theme of "my life" – the "I" being the center of the discourse – but also the production of the identity effect between: the enunciator and the narrator, the narrator and the protagonist, the protagonist and the enunciator. The study of the books that make up the Pedro Nava’s Memories shows that, from the second half of Galo-das-trevas (the fifth volume), the triple identity effect is not completely achieved. By analyzing the discursive syntax and semantics, this paper discusses the labyrinthine mechanisms that break the constraints in the autobiographical genres and their effects of sense.